Strategic Public Communication in Urban Governance: A Study on Government–Citizen Interaction in Bekasi City - Susanti, Eva; Fahmi, Ade; Sa’adih, Sa’adih (JURNAL SOSIAL DAN HUMANIS SAINS, 2022)
This research explores the dynamics of public communication between the local government of Bekasi City and its citizens, focusing on how communication strategies affect public trust, participation, and service responsiveness. Utilizing a qualitative approach through interviews and document analysis, the study finds that while digital platforms such as social media and city service applications have improved access to information, gaps remain in message clarity, audience targeting, and feedback integration. The research contributes to the understanding of effective government-citizen communication as a vital element in democratic urban governance.